Innovative Banking Practices & Customer Satisfaction – A Study With Reference To Selected Customers of Corporation Bank, Mangalore: An analysis of the impact of innovative banking technologies on customer satisfaction (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Technology has brought tremendous changes in the lifestyle of people around the globe. Banking Industry also has witnessed rapid changes in every dimension. Change has become the order of the day. Introduction of new technologies contributed to the growth of banking sector which in turn contributed to the economic development of the country by leading to high capital formation in the country. Satisfying the ever changing customer needs has become a major concern for all banking organizations as the customers play a vital role in their success and survival in the modern competitive business field. Every day, banking. Organizations therefore are looking for innovative ways to satisfy customer needs in order to retain them and to maintain competitive advantage. Banks in India have changed in their operations and moved towards universal banking along with the increased usage of technology and technology-based services, offering alternate channels such as smart cards, ATMs, usage of the internet, mobile and social banking. Corporation Bank being one of the leading banks in the public sector of India has introduced a series of new technologies in its banking operations. This paper highlights the impact of innovative banking technologies on selected customers of one of its branches located in M.G. Road Mangalore. An attempt is made to understand the level of customer satisfaction regarding the latest services offered by the branch.